Pengaruh Lingkungan,Kepuasan dan Pelatihan Kerja Terhadap Kinerja Pegawai - Mila Sartika; Eva Ria Awaliyah; Melati Oktafiyani (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
The company's long-term goal is to maximize employee performance, namely by improving the work environment, job satisfaction and job training so that the company's goals will be achieved. This study aims to analyze the influence of the work environment, job satisfaction and job training on employee performance in the Central Java Maritime Affairs and Fisheries Service. The population in this study amounted to 280 employees, using a sample of 165 employees. Methods of data analysis using multiple linear regression. The results of this study are that the work environment, job satisfaction and job training have a positive effect on employee performance